Metode Integratif Takhrīj Hadis: Prosedur Sistematis Penelusuran Sanad dan Matan dalam Studi Interdisipliner - Surya, Muhammad; Pransetia, Arya Handika; Harahap, Selfi Anna; Uzmanarati, Ulya (Yayasan Albahriah Jamiah Indonesia, 2025)
Methodological fragmentation in the practice of takhrīj hadith remains a fundamental problem in contemporary hadith studies, primarily due to the separation of sanad analysis and matn analysis, which proceeds partially and uncoordinated within a unified procedural framework. This condition results in a weak consistency in the historical assessment of hadith and limits the analytical exploration of the dynamics of transmission and the construction of hadith meaning. This article aims to formulate an integrative and systematic takhrīj hadith method by positioning sanad and matn analysis as two interrelated dimensions in an interdisciplinary study process. This study uses a qualitative research type based on a literature study with the main data sources being classical and contemporary works in the science of hadith, as well as supporting literature from historical and social science studies. The analytical approach is carried out through the integration of sanad criticism, matn criticism, and contextual reading of the social, intellectual, and historical conditions of the narration. The results show that the integrative takhrīj hadith method has the main character of a logical unity between the verification of transmission lines, evaluation of the coherence and substance of matn, and analysis of the context of hadith production and reproduction. The stages of this method include comprehensive mapping of the sanad, examining the relationship between the sanad and the text (matn), and synthesizing contextual analysis as the basis for historical assessment of hadith. This integration forms a methodological logic that is not linear, but rather dialogical and reflective. The implications of this research emphasize the importance of reformulating the takhrīj hadith methodology to be more adaptive, systematic, and relevant for the development of contemporary hadith studies oriented toward historical accuracy and analytical rigor.